АЖИНИЁЗ ВА ҚОРАҚАЛПОҚ АДАБИЙ ТИЛИ - Қарлибаева, Г. (SCIENCE and SOCIETY, 2024)
The article is devoted to semantic peculiarities of literary works of classic poet of Karakalpak literature Ajiniyaz. Polysemantic words, metaphors and metaphoric thinking were investigated. Peculiarities of using Polysemantic words were determined and there were given good examples of metaphors.
Keywords: meanings of word; different meanings of words; polysemy; semantics; metaphor; metonimy